Strategy strikes back how Star Wars explains modern military conflict - Brooks, Max 1972-; Amble, John; Cavanaugh, Matthew L.; Gates, Jaym (Potomac Books, 2018)
"This book addresses real-life applications of the "Star Wars" saga, from the political fallout of targeting civilians, to toxic top-down leadership, to the long-term consequences of abandoning postwar allies" ...